Contemporary Issues in Dealing with Stray Animals: A Comparative Legal Perspective - Anisimov, Aleksej Pavlovič (Journal of applied animal ethics research, 2025)
The purpose of this article is to conduct a legal analysis of the current Russian model for dealing with animals without owners (stray animals) and to evaluate its advantages and disadvantages. The authors demonstrate that the measures taken by the authorities are insufficient to reduce the number of stray animals. The problem must be viewed in the broader context. We propose a set of organisational measures, including compulsory registration of all domestic animals, a change in waste-management policy, the addition of new offences to the Code of Administrative Offences of the Russian Federation, and the settlement of ownership of stray animals (the optimal solution is to assign them to municipal ownership, thereby codifying existing judicial practice of awarding compensation against municipalities for non-pecuniary damage suffered by citizens bitten by stray dogs). Informational, educational and cultural initiatives aimed at fostering a humane attitude towards animals are also required. Our findings may be of interest to countries facing similar challenges.